2010
DOI: 10.1007/s12149-010-0364-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of dopamine transporters in human brain using [11C]PE2I and positron emission tomography: evaluation of reference tissue models

Abstract: Due to the [(11)C]PE2I kinetics in the cerebellum and limited scan duration for (11)C, MRTMo and SRTM underestimated the striatal DVR. Despite this limitation, the present study demonstrated the applicability of reference tissue models. Since DAT in the midbrain and thalamus is of interest in the pathophysiology of neuropsychiatric disease, this noninvasive quantitative analysis will be useful for clinical investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…In human PET studies, 11 C-PE2I showed a high specific-to-nonspecific ratio (15)(16)(17)(18). However, 2 problems have been reported in quantifying DAT with 11 C-PE2I.…”
Section: F-(e)-n-(3-iodoprop-2e-enyl)-2b-carbofluoroethoxy-3b-(4-methmentioning
confidence: 99%
See 3 more Smart Citations
“…In human PET studies, 11 C-PE2I showed a high specific-to-nonspecific ratio (15)(16)(17)(18). However, 2 problems have been reported in quantifying DAT with 11 C-PE2I.…”
Section: F-(e)-n-(3-iodoprop-2e-enyl)-2b-carbofluoroethoxy-3b-(4-methmentioning
confidence: 99%
“…In nonhuman primates, 18 F-FE-PE2I showed faster kinetics and less production of radiometabolites that could potentially permeate the blood-brain barrier than did 11 C-PE2I. The aims of this study were to examine the quantification of DAT using 18 F-FE-PE2I and to assess the effect of radiometabolites of 18 F-FE-PE2I on the quantification in healthy humans. Methods: A 90-min dynamic PET scan was obtained for 10 healthy men after intravenous injection of 18 F-FE-PE2I.…”
Section: F-(e)-n-(3-iodoprop-2e-enyl)-2b-carbofluoroethoxy-3b-(4-methmentioning
confidence: 99%
See 2 more Smart Citations
“…With a 60-min imaging time, BPND of striatum were approximately 103% of that of a 90-min imaging time. 13 (12,14,15,(29)(30)(31). Considering that in vitro DAT DAT is also known to localize in the midbrain, which contains dopaminergic cell bodies.…”
Section: Imaging Time Dependency Of Striatal Bpndmentioning
confidence: 99%